From City of God to City of Men: The Representation of Violence in Brazilian Cinema and Television - Borges, Gabriela (Cinémas, 2011)
This paper discusses the representation of violence in Brazilian cinema and television through analysis of the TV series City of Men (2003-7), which is a follow-up to the film City of God (2002), with the same actors, sets and non-linear narrative. The project began with the production of the TV episode Palace II (2000), which was developed into City of God’s script. After receiving international acclaim, it resulted in the production of City of Men. In this context, it is important to emphasise the relationship between cinema and television and their particular features as products of the Brazilian audiovisual industry’s renaissance in the 1990s. The representation of violence is analysed not only as a thematic issue common to Brazilian favelas but also as an aesthetic element of TV drama. The representation of the oppressed has been well known in Brazilian cinema since Glauber Rocha’s manifesto “Aesthetics of Hunger” (1965), in which he argues that films need to be aggressive in order to truly expose poverty. The main point to be addressed, however, is whether the representation of violence in this series conveys, criticises or reflects about what is really happening in Brazilian favelas or if it merely offers an aesthetic look into poverty for the delight of audiences in Brazil and abroad.